Efektifitas Penggunaan Problem Based Learning Berbasis Media Kerang Terhadap Minat Belajar Perkalian Bagi Murid Kelas III SD - Sandra Tehuayo; Triwiyono Triwiyono; Suwita Suwita; Wigati Yektiningtyas (Jurnal Ilmiah Telaah, 2026)
This study aimed to analyze the effectiveness of a shell-media-based Problem Based Learning (PBL) model in improving multiplication learning interest among third-grade students at SD YPPK St. Yosep Tipuka-Timika. The research employed a quantitative approach using a Pre-Experimental One-Group Pretest–Posttest Design. The sample consisted of 25 students selected through purposive sampling. Data were collected using a mathematics learning interest questionnaire covering the dimensions of enjoyment, attraction, attention, and involvement. Data analysis was conducted using descriptive statistics and inferential statistics through the Shapiro–Wilk normality test and paired sample t-test. The results showed that the average learning interest score increased from 31.24 in the pretest to 45.88 in the posttest, representing a 46.86% improvement. The paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between students’ learning interest before and after the treatment. Furthermore, the distribution of learning interest categories changed substantially, with 64% of students initially categorized as having low learning interest, while 88% were categorized as having high learning interest after the intervention. Therefore, the shell-media-based Problem Based Learning model was proven effective in enhancing elementary school students’ interest in learning multiplication.